PERAN ZAKAT, INFAQ DAN SHADAQAH DALAM KEHIDUPAN - Ubabuddin; Umi Nasikhah (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2021)
Al-Qur'an, through a series of verses, also lays down a series of basic norms for several types of transactions, both general and specific. Includes basic norms relating to several types of economic transactions. Therefore, the absorption of the texts of the Al-Qur'an into a legal compilation including economic and financial verses on the compilation of Islamic economic law will certainly experience difficulties. However, it is substantially based on the legal istinbath (istinbath al-ahkam) of the existing economic law verses, it is very possible. The possibility that the compilation of the Qur'anic texts will be absorbed into the compilation of Sharia economics, really depends on the compilation model itself. This includes emphasizing balance in life, not only focusing on or emphasizing the relationship of a servant with God (ta'abbudi), but also social (ijtimaiyyah). Such as zakat, infaq, shadaqah to improve welfare. Welfare is one of the top priorities of Muslims